2009
DOI: 10.1155/2009/101659
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein as an Anti-Inflammatory Mediator

Abstract: The integration of knowledge concerning the regulation of MT, a highly conserved, low molecular weight, cystein-rich metalloprotein, on its proposed functions is necessary to clarify how MT affects cellular processes. MT expression is induced/enhanced in various tissues by a number of physiological mediators. The cellular accumulation of MT depends on the availability of cellular zinc derived from the diet. MT modulates the binding and exchange/transport of heavy metals such as zinc, cadmium, or copper under p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 67 publications
4
95
0
7
Order By: Relevance
“…MT exhibits antioxidant (Miles et al 2000) and antiinflammatory properties (Inoue et al 2009). We have previously shown that the APOE4 genotype is associated with an altered inflammatory response ) and differences in the cellular oxidant/antioxidant status (Dietrich et al 2005;Jofre-Monseny et al 2008a;Huebbe et al 2007) in cultured cells, mice and humans.…”
Section: Discussionmentioning
confidence: 97%
“…MT exhibits antioxidant (Miles et al 2000) and antiinflammatory properties (Inoue et al 2009). We have previously shown that the APOE4 genotype is associated with an altered inflammatory response ) and differences in the cellular oxidant/antioxidant status (Dietrich et al 2005;Jofre-Monseny et al 2008a;Huebbe et al 2007) in cultured cells, mice and humans.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that metalloteoneins (MTs) are a group of ubiquitous low-molecular-weight proteins essential for the protection of cells against heavy metal ion toxicity. These molecules also are directly involved in regulation of cell growth, differentiation and apoptosis in different pathological conditions and in tumour as well (Inoue et al, 2009). Earlier the low level of MT-1 protein was demonstrated in ovarian endometriomas (Wicherek et al, 2006).…”
Section: Regulation Of Apoptosis In the Endometrium Of Women With Endmentioning
confidence: 99%
“…Our results have shown that MT-1 synthesis significant elevated in endometrium of healthy women after its incubation with peritoneal macrophages. It is known that metallothioneins demonstrated strong antioxidant properties and able to scavenge a wide range of reactive oxygen species thus serving as anti-inflammatory mediators (Inoue et al, 2009). So, the increase of MT-1 synthesis in endometrial cells, undergoing apoptosis, might be one of the factors, participating in the development of anti-inflammatory environment in the process of endometrial apoptotic cells uptake by phagocytes.…”
Section: Influence Of Peritoneal Macrophages and Peritoneal Fluid Upomentioning
confidence: 99%
“…Owing to the high inducibility of its expression upon metal exposure, MT has been long given attention as one of core suits for biomarkers to address risks associated with metal-related environmental problems (Sarkar et al 2006). Besides its fundamental roles in the homeostatic regulation of essential metals and detoxification of trace metals, MT plays important roles in host protective pathways under environmentally or physiologically perturbed conditions (Inoue et al 2009;Chiaverini and Ley 2010;Lynes et al 2014). …”
Section: Introductionmentioning
confidence: 99%